MENELAAH ATURAN KOPERASI SYARIAH UNTUK MEMBANGUN SUISTAINABLE ECONOMY BERORIENTASI FALAH DAN MASHLAHAH - Ainur oktania; Arsiska Sari; Dwi Silfani; Gresia Septina Sitohang; Windi Octaviani; Frandika Situmorang; Ferozi Ramdana Irsyad; Noni Rozaini (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The aim of this research is to look at the rules governing sharia cooperatives and how they affect long-term economic development. The main issues discussed are the laws and regulations governing the operation of sharia cooperatives, the application of the principles of falah and mashlahah, as well as challenges that may arise in achieving the goals of sustainable economic development. The research approach used is a literature review, which involves assessing relevant secondary data, such as government policies and market conditions, to determine the efficiency of implementing sharia cooperative laws. The findings of this research contribute to a better understanding of the role of sharia cooperatives in a sustainable economy, as well as how Islamic principles can be utilized effectively in current economic activities.